Assertive Speech Acts Performed by Teacher in EFL Classes - Milal, Ahmad Dzoul; Kusumajanti, Wahju (NOBEL: Journal of Literature and Language Teaching, 2020)
One of the factors affecting language teaching and learning is the way how the communication process between teacher and learners takes place in the classroom. In a language instructional context, the teacher’s language serves several functions: transactional, interactional, regulatory, as a language model, and linguistic input. These multiple functions give rise to the performance of varied speech acts. This paper tries to reveal the variety of assertive acts and how they are performed by the teachers. After the data were collected by observation and recording and analyzed using a qualitative technique, it was revealed that the assertive speech acts are realized in terms of informing, describing, exemplifying, explaining, concluding, summarizing, commenting, responding, extending, giving feedbacks, giving clues, announcing a topic, announcing a task, and controlling/shifting a topic. The performance of those acts is always consistent with the main purpose of EFL, i.e., elevating the learners’ competence (knowledge and ability) of the target language.